Changes in Addressing Inequalities in Access to Hospital Care in Andhra Pradesh and Maharashtra States of India : A Difference-in-Differences Study Using Repeated Cross-Sectional Surveys - Rao, Mala; Katyal, Anuradha; Singh, Prabal V.; Samarth, Amit; Bergkvist, Sofi; Kancharla, Manjusha; Wagstaff, Adam; Netuveli, Gopalakrishnan; Renton, Adrian (BMJ Publishing Group, 2015)
This article compares the effects of the Rajiv Aarogyasri Health Insurance Scheme of Andhra Pradesh (AP) with health financing innovations including the Rashtriya Swasthya Bima Yojana (RSBY) in Maharashtra (MH) over time on access to and out-of-pocket expenditure (OOPE) on hospital inpatient care. We used two cross-sectional surveys: as a baseline, the data from the NSSO 2004 survey collected before the Aarogyasri and RSBY schemes were launched; and as postintervention, a survey using the same methodology conducted in 2012.